A minimal benzo[c][1, 2, 5]thiadiazole-based electron acceptor as a third component material for ternary polymer solar cells with efficiencies exceeding 16.0%. Issue 1 (5th August 2019) - Ma, Yunlong; Zhou, Xiaobo; Cai, Dongdong; Tu, Qisheng; Ma, Wei; Zheng, Qingdong
Abstract : A simple small molecule of BTF is used as a third component in the binary blends of J71:ITIC and PM6:Y6 to achieve efficient ternary polymer solar cells with enhanced PCEs of 12.35% and 16.53%, respectively. Abstract : Ternary polymer solar cells (PSCs) with three active layer components (two donors with one acceptor, or two acceptors with one donor) have been demonstrated as an emerging strategy to improve the power conversion efficiencies (PCEs). So far, most of the third components utilized in the ternary PSCs are relatively complex molecules or polymers which are expensive due to complicated multi-step syntheses. Here, a simple small molecule of 4, 7-bis(5-bromothiophen-2-yl)-5, 6-difluorobenzo[ c ][1, 2, 5]thiadiazole (BTF), is first used as a second acceptor material to fabricate efficient ternary PSCs. The incorporation of BTF into a binary active layer based on a wide-bandgap polymer of J71 and a low-bandgap acceptor of ITIC, results in ternary PSCs with the best PCE of 12.35%, which is higher than the control J71:ITIC-based binary device with the best PCE of 10.79%. This significantly enhanced PCE results from the simultaneously improved short-circuit current density, open-circuit voltage, and fill factor in the ternary PSCs, and they are in part attributed to the increased light-harvesting with the BTF incorporation and in part attributed to the more balanced charge transportation induced by the improved polymer crystallinity. To determine the generality of BTF as a second acceptor in ternary PSCs, another benchmark binary active layer of PM6:Y6 has been incorporated with 10 wt% BTF, leading to a best-performance device with an outstanding PCE of 16.53% which is the highest among all ternary PSCs, to the best of our knowledge. Our work provides a simple strategy to efficiently boost the performance of ternary PSCs by using an easily available, low-cost acceptor of BTF.